Empirical performance evaluation of raster-to-vector conversion methods: A study on multi-level interactions between different factors - Al-Khaffaf H.S.M.; Talib A.Z.; Salam R.A. (Institute of Electronics, Information and Communication, Engineers, IEICE, 2024)
Indexed by WOS/ Scopus